2019
DOI: 10.3390/electronics8050530
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Audio Encryption Algorithm with Permutation-Substitution Architecture

Abstract: In this paper, a new cryptographic method is proposed, designed for audio files’ security. The encryption algorithm is based on classic symmetric models using pseudo-random number generator composed with chaotic circle map and modified rotation equations. The scheme of a new pseudo-random generator is presented and used as basis for chaotic bit-level permutations and substitutions applied to audio files structure for successful encryption. The audio encryption and decryption algorithms are described and explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 19 publications
2
32
0
4
Order By: Relevance
“…The main difference with true random generators (TRG) is that PRG are software realized and have significantly less cost for implementation. The examples for PRG are presented in [7,8,9] and [10]. The examples demonstrate that using chaotic maps is a successful model in constructing pseudorandom generators.…”
Section: Pseudorandom Generator Modelmentioning
confidence: 99%
“…The main difference with true random generators (TRG) is that PRG are software realized and have significantly less cost for implementation. The examples for PRG are presented in [7,8,9] and [10]. The examples demonstrate that using chaotic maps is a successful model in constructing pseudorandom generators.…”
Section: Pseudorandom Generator Modelmentioning
confidence: 99%
“…The security level (i.e., complexity) of the security algorithm seems to have an impact on these measurement factors [8,13,14]. Constructing new speech encryption algorithms based on chaos theory to increase the security level has drawn for many scientists and researchers attention [15][16][17][18][19][20][21], but unfortunately some of these constructed algorithms have a number of practical problems in terms of cryptanalysis attacks [22,23]. In this paper, a new dynamic speech encryption algorithm using Lorenz chaotic map over IP network is proposed.…”
Section: Figure 1 Taxonomy Of Cryptologymentioning
confidence: 99%
“…Most of the conventional cryptographic algorithms are built to protect the content test messages which are not suitable for multimedia data (i.e., speech) during communication because it involves some inherent features such as encryption and decryption process of speech is different from that test messages, and data redundancy [6]. In recent years, extensive studies have been observed in the research community to apply a various algorithms based on chaos cryptographyto design a robustness crypto-system for multimedia data due to it is desirable features such as non-linear, deterministic, aperiodicity, sensitivity to initial conditions, and un-regular behaviours (i.e., random-like performance) [6][7][8][9][10][11][12][13][14], but unfortunately there are fundamental drawbacks in these chaotic crypto-systems in terms of cryptanalysis attacks (i.e., low level of security, and small key space) [15,16]. In general, chaotic crypto-systems can be classified into three categories based on their structure (i.e., analogue, or digital chaotic) each category represented by different In this paper we have used chaos based cryptography (i.e., chaotic cryptography) to propose a new dynamic speech crypto-system using Hénon chaotic map to overcome the aforementioned drawbacks.…”
Section: Introductionmentioning
confidence: 99%